Surgical management of papillary thyroid carcinoma - Elgamal, Wael M.; Ragheb, Ragheb A.; Elsharkawy, Ashraf (International Surgery Journal, 2021)
Background: Papillary thyroid carcinoma (PTC) is the most prevailing thyroid cancer but remains of a favorable prognosis. Thyroidectomy with excision of all positive cervical nodes remains the cornerstone of the management PTC. The role for prophylactic central neck dissection (PCND) remains controversial. Methods: A prospective non randomised open label study of 20 PTC patients, 8 of them underwent total thyroidectomy with PCND and 12 underwent total thyroidectomy with modified radical neck dissection type III in El Zahraa hospital, Azhar university, and Damanhour oncology center, Egypt starting from September 2019 to August 2021. The incidence of central lymph node metastasis in N0 cases underwent PCND were reported, the relationship between lymph node metastasis with lympho-vascular permeation and capsular invasion, were analysed and sensitivity of fine needle aspiration cytology in diagnosis of PTC was reported. Results: Occult central lymph node metastasis was observed in 62.5% of PTC lesions. The FNAC showed a sensitivity of 85%. Lympho-vascular permeation and capsular invasion showed a sensitivity of 94.12% and 58.82%, respectively for lymph nodes metastasis. Thyroiditis is detected in 50% of cases with PTC. Postoperative ablative dose of radioactive iodine 131 (RAI-131) ranged from 80 to 100 millicurie. Conclusions: R0 resection is mandatory to cure PTC. PCND remains a debatable issue, that needs a large multicentre study with large sample of patients with long term follow up to ascertain the efficacy of PCND in reducing rate of local recurrence, morbidity and mortality.